(untitled) (Research, Society and Development, 2021)
Objective: To characterize the microbiota of complex wounds and the antimicrobial resistance of the microorganisms found. Methods: Cross-sectional, observational and dissertative study, carried out based on the results of microbiological cultures of patients undergoing outpatient follow-up to treat complex wounds. Study approved under CAAE opinion number 93044418.6.0000.5013. Results: 110 tests were analyzed, collected from vasculogenic, diabetic, pressure ulcer, surgical, oncological, acute, anthrax lesions, fournier syndrome and marjolin ulcer. 22 species of bacteria were identified, 18 Gram-negative and 4 Gram-positive, with predominance of Pseudomonas aeruginosas, Proteus mirabilis and Staphylococcus aureus. All the microorganisms identified showed resistance to at least one antimicrobial, the P. mirabilis species being resistant to a greater number of antibiotics. Conclusion: This study points out that the complex wound microbiota is predominantly composed of Gram-negative microorganisms, the species P. aeruginosa stands out. Antimicrobial resistance was detected in all microorganisms found.